Two Pediatric Cases of Primary Ciliary Dyskinesia Caused by Loss-of-Function Variants in Oral-Facial-Digital Syndrome Gene, OFD1 - Yifei Xu; Yuki Tsurinaga; Tsubasa Matsumoto; Ryuji Muta; Taichi Yano; Hiroshi Sakaida; Sawako Masuda; Koki Ueda; Guofei Feng; Shimpei Gotoh; Satoru Ogawa; Makoto Ikejiri; et al. (Case Reports in Genetics)
Primary ciliary dyskinesia (PCD) is a hereditary disease caused by genes related to motile cilia. We report two male pediatric cases of PCD caused by hemizygous pathogenic variants in the OFD1 centriole and centriolar satellite protein (OFD1) gene. The variants were NM_003611.3: c.[2789_2793delTAAAA] (p.[Ile930LysfsTer8]) in Case 1 and c.[2632_2635delGAAG] (p.[Glu878LysfsTer9]) in Case 2. Both cases had characteristic recurrent respiratory infections. Neither case had symptoms of oral-facial-digital syndrome type I. We identified a variant (c.2632_2635delGAAG) that has not been previously reported in any case of OFD1-PCD.